APPROACH TO INTERACTIVE DANCE AND DIGITAL DANCE CREATION: REVIEW OF PROPOSALS AND FUTURE LINES. (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
The multidisciplinary scenic proposals of connection between dance, body, video, and interactive devices present reflections on the classical difference between the rational and the emotional, the physical and the intangible. Interactive dance is a type of audiovisual performance, with precedents in video dance, live cinema, and other performative practices, which in recent years has gathered the functions of code as a cultural form. Digital audiovisual creation is a field of high potential, due to its transdisciplinary capacity. If the creation with code was created as a problem or matter of disciplines such as engineering, it has moved to the whole field of artistic practices. Through these projects, the creation with code is one more of the wide range of perspectives that are found in the field of interactivity between digital systems and scenic practices, collecting at the same time a whole legacy of relationship between dance and technology - which collaborates with it more than being a tool at its disposal.In the paper, a critical analysis of works of interrelation between dance and audio-visual proposals is made, with mention of the possibilities for composition, improvisation, and interpretation which companies and audio-visual collectives are already using, along with a brief reflection on its future.
Keywords: interactive dance; creation with code; programming software; video dance